2017
DOI: 10.3390/su9050851
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Effectiveness of Irrigated Area Expansion in Mitigating the Impacts of Climate Change on Crop Yields in Northern China

Abstract: Abstract:To improve adaptive capacity and further strengthen the role of irrigation in mitigating climate change impacts, the Chinese government has planned to expand irrigated areas by 4.4% by the 2030s. Examining the adaptive potential of irrigated area expansion under climate change is therefore critical. Here, we assess the effects of irrigated area expansion on crop yields based on county-level data during 1980-2011 in northern China and estimate climate impacts under irrigated area scenarios in the 2030s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…With the available groundwater resources becoming scarce with an increasing temperature, there is an urgent need to improve irrigation efficiency (Gou et al, 2020). Farmers also need to take adaptive measures by increasing irrigation frequency and expanding irrigated areas to mitigate production risks resulting from extreme drought events (Zhang et al, 2017;Wang et al, 2018Wang et al, , 2019aWang et al, , 2019bZhang et al, 2020). Rapid urbanization and industrialization will increasingly use more water and decreasing water resources will force agriculture to reduce its water usage.…”
Section: Introductionmentioning
confidence: 99%
“…With the available groundwater resources becoming scarce with an increasing temperature, there is an urgent need to improve irrigation efficiency (Gou et al, 2020). Farmers also need to take adaptive measures by increasing irrigation frequency and expanding irrigated areas to mitigate production risks resulting from extreme drought events (Zhang et al, 2017;Wang et al, 2018Wang et al, , 2019aWang et al, , 2019bZhang et al, 2020). Rapid urbanization and industrialization will increasingly use more water and decreasing water resources will force agriculture to reduce its water usage.…”
Section: Introductionmentioning
confidence: 99%
“…Mottaleb et al [28] investigated over 800,000 farmers in Bangladesh on machinery adoption and found out that physical assets, institutional and physical infrastructure positively affect adoption. It is the same with the irrigation system [29]. Also, women farmers are less likely to own agricultural assets than men.…”
Section: Literature Reviewmentioning
confidence: 98%
“…A considerable amount of research work conducted in recent years has evaluated the effect of VPD on transpiration, plant grown and production, and water productivity. VPD has been widely recognized as the driving force of water loss from a leaf and a parameter describing the climate conditions favorable for the development of fungal crop diseases and several crop physiological disorders [72,73]. Optimal VPD values for tomato and cucumber are suggested to be in the range of 0.3 to 1.0 kPa [52].…”
Section: Microclimatic Conditionsmentioning
confidence: 99%